Pengaruh Durasi Penggunaan Smartphone Di Kalangan Pelajar Terhadap Frekuensi Nyeri Leher - Wibisono, Irawan; Purnomo, Didik; Amanati, Suci (UI Scholars Hub, 2023)
Neck pain is a musculoskeletal problem that is often encountered in productive age, one of the triggers for neck pain is an unergonomic position for a long time. For example when using a smartphone, the position of the neck will tend towards the front. The use of smartphones in this technological era takes a long time. This is because smartphones have become part of student life. This study aims to determine the effect of the duration of smartphone use on the frequency of neck pain. This research method uses descriptive cross sectional with a total sample of 68 people, while the research sample is students studying in Semarang. The results showed that 55% of the sample used a smartphone with a duration ranging from 4-8 hours and as many as 35% of the sample experienced pain frequency less than 1 time per month and the results of the bivariate analysis of this study found that the correlation between the duration of smartphone use and neck pain was 0.160 with a significance between the two variables of 0.211. Based on the results of the study it can be concluded that the duration of smartphone use will affect the level of neck pain frequency with the correlation between the two variables being unidirectional, which means that the longer you use a smartphone, the higher the frequency of neck pain and the lower the significance level between the two variables. So it is necessary to carry out further research with a larger number of samples and more in-depth analysis.